Fibroblast growth factor 21 resistance is associated with body shape in patients with type 2 diabetes complicating hypertension - Gan, Jing; Duan, Zikun; Tang, Lu; Liu, Zhen; Tian, Huiying; Wu, Maolan; Bi, Yanxue; Pan, Xingchao; Wang, Wenjun; Gao, Xiaotang; Wang, Ningrui; Lin, Zhuofeng; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objectives Obesity, especially abdominal obesity, increases the prevalence of metabolic and cardiovascular disease (CVD). Fibroblast growth factor 21 (FGF21) has been identified as a critical regulator playing a therapeutic role in diabetes and its complications. This study aims to evaluate the relationship between serum FGF21 levels and body shape parameters in patients with hypertension (HP) and type 2 diabetes mellitus (T2DM). Methods Serum FGF21 levels were determined in 1,003 subjects, including 745 patients with T2DM, and 258 individuals were selected as a healthy control in this cross-sectional study. Results Serum FGF21 levels were significantly higher in T2DM patients with HP than those without [534.9 (322.6–722.2) vs. 220.65 (142.8–347.55) pg/ml, p < 0.001], and levels in both of these two groups were significantly increased compared with that of healthy control [123.92 (67.23–219.32) pg/ml, all p < 0.001]. These differences were also observed in body shape parameters, including weight, waistline, body mass index (BMI), body shape index (ABSI), and the percentage of abdominal obesity. Serum FGF21 levels in T2DM patients were positively correlated with body shape parameters, including weight, waistline, neck circumference, BMI, ABSI, percent of abdominal obesity, and triglyceride, while negatively with estimated glomerular filtration rate (all p < 0.01). The significance remained stable when adjusted for age and T2DM duration. In addition, both serum FGF21 concentrations and waistline were independently associated with HP in T2DM patients after the adjustment for risk factors (all p < 0.05). ROC analysis for FGF21 levels of 745 patients with T2DM identified 411.33 pg/ml as an optimal cut-off point to predict HP, with a sensitivity and specificity of 66.0% and 84.9%, respectively. Conclusions FGF21 resistance occurs in patients of HP in T2DM, and positively correlates with body shape parameters (especially waistline and BMI). High levels of FGF21 may be a compensatory reaction to offset HP.